Three Case Studies of Community Occupational Therapy for Individuals with Human Immunodeficiency Virus. Issue 1 (2nd January 2015) - Misko, Alexis N.; Nelson, David L.; Duggan, Joan M.
ABSTRACT Three case studies illustrate the complexities and opportunities in providing community-based occupational therapy services to persons with HIV. An infectious disease physician recommended three clients for therapy sessions in both the home and community. The Model of Human Occupation (MOHO) in conjunction with the Conceptual Framework for Therapeutic Occupation (CFTO) was used to guide the therapeutic process. Assessments measured challenges to clients and client progress in the following areas: leisure, mobility, organization, problem solving, community involvement, transitioning to independent living, fatigue, childcare/play, and home management. This paper describes the three cases with findings suggesting that community-based occupational therapy has potential to address important issues such as habits, roles, and volition in the HIV/AIDS population.